98 Parental perspective on changes in health care following integration to a complex care program. (29th October 2021) - Thibault, Louis-Philippe; Marano, Maria; Saad, Lydia; Gaucher, Nathalie; Couture, Karine; Doré-Bergeron, Marie-Joëlle; Chartrand, Caroline; Fregeau, Sandra; Bourque, Claude-Julie; Kleiber, Niina
Abstract: Primary Subject area: Complex Care Background: Quantitative studies have found that integration into a complex care program (CCP) leads to decreased number of visits to the emergency department (ED) and hospitalization days for children with medical complexity (CMC). However, little is known about CMC families' experiences regarding their healthcare resource utilization patterns following their child's integration in the CCP. Objectives: To analyze parental perspectives regarding changes in healthcare resources utilization following CCP admission. Design/Methods: This study was conducted in our tertiary care pediatric university hospital, between December 2019 and January 2021 using individual semi-structured interviews. To assess the effect of CCP admission on healthcare resources utilization, only patients with at least 6 months of chronic disease before inclusion were eligible (32 families). The interview guide was co-constructed by our CCP team of nurses, doctors, social worker and parents of CMC. Participation rate was over one third (12/32) throughout, for which a satisfactory level of data saturation was obtained, as core themes specific to the research question were repeatedly identified. Verbatims were analyzed with NVivo. Descriptive thematic analysis was performed by coding themes emerging from the data. Results: Sixteen parents from twelve families were interviewed (11 mothers, 5 fathers, including 4 couples). Most parents had experienced a decrease in ED visits with improvement in their perceived satisfaction regarding the provided healthcare services following CCP admission. Visits to the CCP pediatrician led to appreciated, continuous and tailored care. In comparison, the constant change of pediatricians in the ED and during hospitalization on the ward seemed to complicate their care experience. Also, the support from pivot nurses and social workers for daily health issues, drug prescription and paperwork was perceived as a relief. This directly favorably influenced care experience. Profound knowledge of patients' health conditions and families' personal challenges and strengths, led to personalized care and trust that greatly improved parents' confidence in care and empowered families. Individualized advice by the CCP team leading to prompt treatment and preventive measures started early at home were identified by parents as the main driving forces leading to the observed decrease in ED visits. When hospitalized, confidence in the quality of care provided by parents at home with close follow-up by CCP were identified as the main driving forces leading to the quicker discharge. Conclusion: Changes in health care utilization following admission to CCP was associated with an improved care experience. Parents identified individualized care and close follow-ups as key factors leading to decreased health care utilization.